Process Design of Microbiological Chitin Extraction - BUDIASIH WAHYUNTARI; . JUNIANTO; SISWA SETYAHADI (Microbiology Indonesia, 2011)
Chitin extraction from shrimp shells involves two processing steps, these are the deproteination and demineralization process. The aim of this experiment was to compare the order of the chitin extraction process. The first experiment was deproteination of fresh shrimp shells followed by demineralization process and the second one was demineralization of fresh shrimp shells followed by deproteination. Bacillus licheniformis F11.1, a proteolytic producing bacterium, was used for the deproteination process. Lactobacillus acidophilus FNCC116, a lactic acid bacterium, was used for the demineralization process. The deproteination was done in a 1 liter fermenter jar at 55 ºC, 250 rpm and 2.5 vvm aeration for 60 h. The demineralization was done in the same size fermenter at 30 ºC and 50 rpm agitation for 48 h. The experimental results showed that demineralization followed by the deproteination process resulted in a better chitin yield than when the process was conducted in the opposite order. The first process reduced 47.37% protein and 50.23% ash, whereas the second process reduced 79.61% protein and 88.65% ash